Sun‐related behaviours among young Australians with Asian ethnic background: differences according to sociocultural norms and skin tone perceptions. (29th December 2014) - Day, A.K.; Wilson, C.J.; Hutchinson, A.D.; Roberts, R.M.
<x xml:space="preserve">Abstract</x> Deliberate tanning, poor sun protection and sun exposure increase an individual's risk for skin cancer. Recent evidence suggests that individuals of Asian heritage have lower incidence of skin cancer than Caucasians but that their post‐diagnosis outcomes are often worse. In Western cultures tanning behaviours are often motivated by a desire for 'attractive' tanned skin. Conversely, a light complexion is desired in a number of Asian cultures and may consequently serve to protect this group from excessive and risky sun exposure behaviours. This possibility is yet to be tested, with little known about the sun‐related behaviours of Asian people residing in Australia. The present study involves 140 South Australian young adults who report having Asian heritage. Results show that the majority of female participants, and significantly fewer males, reported participating in deliberate outdoor tanning behaviour. Perceptions of family, peer and media tanning norms influenced behaviour, with peer norms being the strongest predictor. The desire for a lighter skin tone was associated with increased sun‐protective behaviour and a lower number of previous severe sunburns. As a significant proportion of participants engaged in deliberate tanning behaviour, it is recommended that future research continue to explore factors associated with tanning, including an explicit measure of culture.